Strategi Sinergi Polri-Tni Melalui Kepemimpinan Lapangan Dan Pengembangan Sdm Dalam Menghadapi Tantangan Global - Laoli, Elvianus; Antariksa, Bambang; Harsono, Gentio (Syntax Literate, 2025)
This research aims to analyze the role and contribution of field leadership in strengthening the synergy between the National Police and the TNI in facing global challenges. The research method used is qualitative phenomenological. Data sources were taken based on interviews with representative informants at the level of National Police Headquarters and TNI Headquarters, Bekasi Resort Police and Sleman Yogyakarta Police, Sleman Dandim and Bekasi Dandim. Research period March - August 2024, data analysis using an interactive model. The results of the research show that future global challenges that will be faced by the National Police and TNI will focus on acts of terrorism, regional conflicts and asymmetric wars, maritime security issues, threats of damage to natural resources, natural disasters, climate change and cyber threats, cross-border crime, trafficking. drugs, acts of separatism and armed crime in addition to conventional threats, both horizontal and vertical. Successful leadership that builds Polri-TNI synergy is leadership that is communicative, collaborative and able to build coordination between the two institutions and other ministries/institutions with a vision of national interests.